Fairy Tale as a Medium for Childrenâs Character Cooperation Building - Sayer, Inaad Mutlib; Kristiawan, Muhammad; Agustina, Mediarita (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
A fairy tale is a fantasy story which gives moral education, and can be one of the media used for character building. One of the values found in a fairy tale is cooperation. Childrenâs character building strategy is done through giving fairy tales, listening to fairy tales, and creating a supportive reading environment. This study aimed at observing the ability of children in identifying the character values found in fairy tales and their ability to implement the values in their daily life. The respondents of this study were 3-4-year-old students of PAUD Pelangi Palembang. The number of the respondents was 15 students. The study used mixed methods. The data were collected through interview, observation and test. The results revealed that the value of cooperation could be effectively implemented through fairy tales. Before they were told fairy tales, the students were reluctant to tidy up their toys after they finished playing together, but after they were given a fairy tale about cooperation, the children enthusiastically cooperated to tidy up their toys, tidy up the classâ benches, throw garbage and tidy up the books on the shelf.